2012
DOI: 10.1016/j.bbabio.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and ion channel gene alterations in autism

Abstract: To evaluate the potential importance in autistic subjects of copy number variants (CNVs) that alter genes of relevance to bioenergetics, ionic metabolism, and synaptic function, we conducted a detailed microarray analysis of 69 autism probands and 35 parents, compared to 89 CEU HapMap controls. This revealed that the frequency CNVs of ≥ 100 kb and CNVs of ≥ 10 Kb were markedly increased in probands over parents and in probands and parents over controls. Evaluation of CNVs ≥ 1 Mb by chromosomal FISH confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Unlike these variations, the third variation F240L showed a significant accelerated time‐dependent inactivation (Breitenkamp et al., 2014; Table 2). A deletion in chromosome region 12p13.33, that affects both the CACNA1C and the CACNA2D4 genes coding for the α 1 channel‐forming subunit and the α 2 δ 4 auxiliary subunit, respectively, was observed in patients with autistic manifestations (Smith et al., 2012). A chromosomal translocation of 2p:12p resulting in a deletion of both genes ( CACNA1C and CACNA2D4 ) was detected in two ASD‐affected individuals (Smith et al., 2012).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike these variations, the third variation F240L showed a significant accelerated time‐dependent inactivation (Breitenkamp et al., 2014; Table 2). A deletion in chromosome region 12p13.33, that affects both the CACNA1C and the CACNA2D4 genes coding for the α 1 channel‐forming subunit and the α 2 δ 4 auxiliary subunit, respectively, was observed in patients with autistic manifestations (Smith et al., 2012). A chromosomal translocation of 2p:12p resulting in a deletion of both genes ( CACNA1C and CACNA2D4 ) was detected in two ASD‐affected individuals (Smith et al., 2012).…”
Section: Reviewmentioning
confidence: 99%
“…A deletion in chromosome region 12p13.33, that affects both the CACNA1C and the CACNA2D4 genes coding for the α 1 channel‐forming subunit and the α 2 δ 4 auxiliary subunit, respectively, was observed in patients with autistic manifestations (Smith et al., 2012). A chromosomal translocation of 2p:12p resulting in a deletion of both genes ( CACNA1C and CACNA2D4 ) was detected in two ASD‐affected individuals (Smith et al., 2012). Furthermore, a whole‐exome sequencing study identified de novo rare alleles in α 1 subunit loci CACNA1D and CACNA1E (O'Roak et al., 2012; Pinggera et al., 2015).…”
Section: Reviewmentioning
confidence: 99%
“…Like LHON (6), in ASDs, males are four times more likely than females to be affected (63,64). Mitochondrial metabolic defects have been repeatedly reported in ASD patients, and mtDNA mutations have been found in several ASD pedigrees (63,(65)(66)(67).…”
Section: The Ndna and Mtdna Genetics Of "Complex" Diseasesmentioning
confidence: 99%
“…Indeed, in one study, an ASD subject with one CNV had near-normal OXPHOS function, while another patient with 13 CNVs had a severe OXPHOS defect (67).…”
Section: The Ndna and Mtdna Genetics Of "Complex" Diseasesmentioning
confidence: 99%
“…The current interpretation of these finding is that causative copy number variants impact specific genetic networks that contribute to optimal neurological function. The 2,000 nuclear genes required for mitochondrial assembly and functions constitute one such network (Smith et al 2012). Chauhan et al 2012 reported that higher levels of mitochondrial free radicals of oxygen were present in lymphoblastoid cells from autism cases versus controls.…”
Section: Mitochondrial Dysfunction In Autismmentioning
confidence: 99%